Tertib Administrasi Pembayaran Retribusi Pasar di Kabupaten Barito Timur Provinsi Kalimantan Tengah - Ambar Ratmoko; Nurma Yunita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study is to explain and describe the Orderly Administration of Market Levy Payments in East Barito District, Central Kalimantan. The type of research used in this study is descriptive with qualitative research methods with observation, interview, and documentation techniques. The data sources in this study are the Head of the Trade Office, the Head of the Market Management Division, the Head of Market Signatures, and the effective Banyan Market Traders. Based on the results of the study showed that the orderly administration of payment of market retribution had not gone well, this is because there are still many unregulated administrative traders every month and related agencies are not strict in taking action against traders who are not orderly administration. Traders complain that the government does not pay attention to market facilities, infrastructure in the form of roads and the level of market cleanliness. Kendal-constraints that prevent the Department of Commerce from carrying out administrative order, namely the lack of employees in the field and lack of assertiveness in carrying out their duties in taking action against traders who are not in orderly administration. The program carried out in carrying out administrative order is to register the name of the merchant and enter it into the database and make a rental contract for shops, market outlets and bases for a period of 2 years